IPPJ Sdn Bhd customer’s satisfaction towards usability of website / Munirah Rahman - Rahman, Munirah (Faculty of Business and Management, 2012)
With the fast development and increasing use of the World Wide Web as both an information seeking and an electronic commerce tool, web usability studies grow in importance. Changing technological advancements and capabilities simultaneously also challenges and frustrates website designers. They face increasingly difficult decisions to choose between an array of features that can make their sites more stimulating, visually pleasing, comprehensive, and commercially viable. Numerous web design checklists have been developed that focus on features that may influence users' satisfaction with the website. This research study plans to systematically investigate features that affect customers’ satisfaction through usability of website. The questionnaire was design for the selected respondents where they were asked varieties of questions regarding features of website usability that satisfy customer. The process of analyzing and interpreting data has been presented with tables using methods such as frequency distribution and correlation.